2015
DOI: 10.1039/c5cp00723b
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive fluorescence-based detection of magnetic field effects in photoreactions of flavins

Abstract: Magnetic field effect studies have been conducted on a variety of flavin-based radical pair systems chosen to model the magnetosensitivity of the photoinduced radical pairs found in cryptochrome flavoproteins. Cryptochromes are blue-light photoreceptor proteins which are thought to mediate avian magnetoreception, an hypothesis supported by recent in vitro observations of magnetic field-dependent reaction kinetics for a light-induced radical pair in a cryptochrome from the plant Arabidopsis thaliana. Many crypt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 50 publications
(94 reference statements)
1
17
1
Order By: Relevance
“…6 for model of the effect of the MF on the cryptochrome photocycle). It should be added that attempts in the literature to link biological magnetosensing to forward electron transfer events in cryptochrome (see, e.g., Solov'yov et al 2007;Maeda et al 2012;Mouritsen and Hore 2012;Dodson et al 2013;Biskup 2013;Evans et al 2015;Hong and Pachter 2015;Lüdemann et al 2015;Müller et al 2015;Bialas et al 2016;Kattnig et al 2016;Nohr et al 2016Nohr et al , 2017Worster et al 2016;Van der Straeten et al 2018) are not supported by the biological data neither in birds (Wiltschko et al 2016) nor (as shown in this study) in plants.…”
Section: Discussioncontrasting
confidence: 56%
“…6 for model of the effect of the MF on the cryptochrome photocycle). It should be added that attempts in the literature to link biological magnetosensing to forward electron transfer events in cryptochrome (see, e.g., Solov'yov et al 2007;Maeda et al 2012;Mouritsen and Hore 2012;Dodson et al 2013;Biskup 2013;Evans et al 2015;Hong and Pachter 2015;Lüdemann et al 2015;Müller et al 2015;Bialas et al 2016;Kattnig et al 2016;Nohr et al 2016Nohr et al , 2017Worster et al 2016;Van der Straeten et al 2018) are not supported by the biological data neither in birds (Wiltschko et al 2016) nor (as shown in this study) in plants.…”
Section: Discussioncontrasting
confidence: 56%
“…As a result, the FMN ground state population is decreased, giving rise to lower uorescence yields in the presence of a eld. 20 Finally, following baseline subtraction and the procedure outlined in the Methods section, the average %MFE can be obtained (Fig. 4b).…”
Section: Resultsmentioning
confidence: 99%
“…The % MFE of À1.25% is in excellent agreement with previous results, obtained by Evans et al in similar solution conditions. 20 Arabidopsis thaliana cryptochrome 1 (AtCry1). Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed UV/Vis absorption and emission (fluorescence) spectra of F10T ( Figure 6) are similar to those of FMN-Trp systems (added separately in solution;F MN = flavin mononucleo- tide) reported previously. [11] While the absorption maximaa re attributable to the S 0 !S 1 (p!p*) transition of the flavin isoalloxazine moiety, the emissions pectrum corresponds to the S 1 !S 0 (p*!p)t ransition also on the flavin isoalloxazine residue. [11] These spectroscopic data showst hat the individual properties of flavin and Trpr emaininvariant in the dyad F10T.…”
mentioning
confidence: 99%